Ecoepidemic models with prey group defense and feeding saturation - Gimmelli, Giacomo; Kooi, Bob W.; Venturino, Ezio (Ecological complexity, 2015)
•Ecoepidemic model for the herd behavior of prey attacked by specialist predators.•Dynamics includes diseased prey and feeding saturation of predators.•Several types of bifurcations are discovered. In this paper we consider a model for the herd behavior of prey, that are subject to attacks by specialist predators. The latter are affected by a transmissible disease. With respect to other recently introduced models of the same nature, we focus here our attention to the possible feeding satiation phenomenon. The system dynamics is thoroughly investigated, to show the occurrence of several types of bifurcations. In addition to the transcritical and Hopf bifurcation that occur commonly in predator–prey system also a zero-Hopf and a global bifurcation occur. The Hopf and the global bifurcation occur only in the disease-free (so purely demographic) system. The latter is a heteroclinic connection for the between saddle equilibrium points where a stable limit cycle is disrupted and where the system disease-free collapses while in a parameter space region the endemic system exists stably.